“Conocimientos y actitudes del personal de salud sobre manejo de residuos hospitalarios servicio de gineco. Obstetricia. Hospital amazonico de yarinacocha octubre 2009 – setiembre 2010” - Montenegro Pinedo, Hermes (2011)
Montenegro Pinedo Hermes, knowledge and attitudes of health workers on management of hospital waste service of obstetrics. Yarinacocha Amazonian hospital. October 2009 - September 2010 ". The purpose of this non-experimental study of simple descriptive design, with samples taking into account personal health of the obstetrics service on management of hospital waste Hospital Amazon of Yarinacocha, was to identify the level of knowledge, trends attitude of health personnel on management of hospital waste service of obstetrics. Hospital Amazon of Yarinacocha. "During the period between September October 2009 - 201 O". 50 workers from health on hospital waste management personnel participated in this study obstetrics service. Yarinacocha Amazonian hospital. October 2009-September 2010 ". The findings suggested that, the level of knowledge of the total number of pers...